RELATIONSHIP BETWEEN PARENTS 'ATTENTION, SOCIAL ENVIRONMENT, AND INDEPENDENCE LEARNING WITH MATHEMATICAL LEARNING OUTRCOME OF STUDENTS IN SMP MUHAMMADIYAH 9 YOGYAKARTA - Lutfi Azmul Fauzi; Abdul Taram (Universitas Ahmad Dahlan, 2017)
The low student mathematics learning outcomes are influenced by many factors. Parental attention, social environment, and learning independence are some of the factors that are thought to influence student learning outcomes in mathematics. Therefore, this study was conducted with the aim of finding out whether there was a positive and significant relationship between parents' attention, social environment and learning independence with mathematics learning outcomes for students of class VIII odd semester of SMP Muhammadiyah 9 Yogyakarta 2016/2017 school year. The population in this study were all eighth-grade students of Muhammadiyah 9 Yogyakarta Middle School 2016/2017 academic year consisting of 5 classes with a total of 182 students. As the sample class VIII D consisting of 36 students using random sampling techniques to the class. The data collection technique was carried out using a questionnaire method for parents' attention, social environment and learning independence. As for the test method for student mathematics learning outcomes. The instrument test uses validity and reliability tests. The analysis prerequisite test uses a normality test, independent test, and linearity test. Analysis of hypothesis testing data uses simple linear regression analysis and multiple regression and correlation analysis. The results showed that there is a positive and significant correlation among parents' attention, social environment and learning independence with mathematics learning outcomes with Fcount = 9,70 > Ftable = 2,90 multiple correlation coefficient (R) is 0,69 and the multiple determination coefficient (R2) is 0,48. While the multiple regression equation is , relatively contribution (X1) = 62,34%, the relative contribution (X2) = 19,18%, the relative contribution (X3) = 18,48% and effective contribution (X1) = 29,68%, the effective contribution (X2) = 9,13%, and the effective contribution (X3) = 8,80%.